2012
DOI: 10.1038/ijos.2012.77
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid etching on marginal adaptation of mineral trioxide aggregate to apical dentin: microcomputed tomography and scanning electron microscopy analysis

Abstract: The present investigation assessed the effect of acid etching on marginal adaptation of white- and gray-colored mineral trioxide aggregate (MTA) to apical dentin using microcomputed tomography (micro-CT) and scanning electron microscopy (SEM). Sixty-four extracted single-rooted human maxillary teeth were used. Following root-end resection and apical preparation, the teeth were equally divided into four groups according to the following root end filling materials: (i) white-colored MTA (WMTA), (ii) etched WMTA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Another approach to assess the sealing ability of a filling material is to determine the quality of marginal adaptation under a SEM (Peters & Peters, ). This method has been used to evaluate the marginal adaptation of root‐end filling materials to the surrounding tooth structure (Al‐Fouzan et al, ; Badr, ; Bidar, Moradi, Jafarzadeh, & Bidad, ; Rosa et al, ; Torabinejad et al, ). The main advantage of SEM is the ability to provide high magnification and good resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to assess the sealing ability of a filling material is to determine the quality of marginal adaptation under a SEM (Peters & Peters, ). This method has been used to evaluate the marginal adaptation of root‐end filling materials to the surrounding tooth structure (Al‐Fouzan et al, ; Badr, ; Bidar, Moradi, Jafarzadeh, & Bidad, ; Rosa et al, ; Torabinejad et al, ). The main advantage of SEM is the ability to provide high magnification and good resolution.…”
Section: Discussionmentioning
confidence: 99%
“…No additional studies were identified after the cross‐reference analysis. Following the full‐text reading, 18 studies were excluded, and the reasons for exclusion were the following: using burs for root‐end cavity preparation , no comparison of MTA with another filling material , inadequate detail regarding root‐end cavity preparation and one study had exactly the same data as a previously published study . Finally, 20 studies were found to be eligible for inclusion in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…For Groups 1 and 3, the roots were obturated using warm vertical condensation of F2 calibrated gutta-percha points (Dentsply-Maillefer, Tulsa, OK) and AH26 sealer (Dentsply-DeTrey, Konstanz, Germany). [ 16 ] After setting of the sealer, teeth were kept in artificial saliva and aerobic environment. Seventy-two hours later, root-end preparations and retrograde fillings were performed by a single operator under a surgical microscope (Global, St. Louis, MO, USA) at× 8 magnification.…”
Section: Methodsmentioning
confidence: 99%